Phylogenenetic approach of the section Bulbocodii D.C. of Narcissus based on cpDNA. A case of taxonomic inflation?. (3rd July 2016) - Fonseca, J. P.; Levy, A.; Henriques, R.; Costa, J. C.; Neto, C.; Robalo, J.
Abstract : In this paper, we analyzed the phylogeny of the section Bulbocodii (genus Narcissus ; Amarillydaceae) using the matK and trnL-F fragments of cpDNA in order to review the validity of the recognized taxa. Our results indicate that Narcissus obesus should be considered a valid species, and that N. blancoi is a distinct taxon . In addition, seven previously recognized species, N. juressianus, N. subnivalis, N. graellsii, N. conspicuus, N. citrinus, N. nivalis, and N. quintanilhae, should be assigned to an infraspecific rank under N. bulbocodium, as they are not valid species. In addition, we analyzed the distribution of the three morphological characters widely used in the systematics of this section and found that their variation does not agree with the phylogenetic results, rendering these characters limited taxonomical utility. This result suggests that the section Bulbocodii shows high morphological lability, which can explain the proliferation of nominal species.